Stored grain pest prevalence and insecticide resistance in Egyptian populations of the red flour beetle Tribolium castaneum (Herbst) and the rice weevil Sitophilus oryzae (L.). (May 2020) - Attia, Manal A.; Wahba, Trandil F.; Shaarawy, Nehal; Moustafa, Fathia I.; Guedes, Raul Narciso C.; Dewer, Youssef
Abstract: As a consequence of the widespread use of insecticides against insect pests in grain warehouses and in the food industry, insecticide resistance has greatly increased among these species all over the world. Nonetheless, insecticide resistance in stored grain insects in Egypt was little studied. Therefore, our study aimed to forecast infestation risks and determine the insecticide resistance level in Egyptian populations of the main insect pests of stored grains. To achieve this goal, we surveyed the populations of stored-product insects in wheat in two different sites in the Alexandria governorate (Egypt) between June and August 2017. Moreover, insecticide resistance levels in Egyptian populations of Tribolium castaneum (Herbst) and Sitophilus oryzae (L.) collected from wheat storage facilities (granaries and flour mills) in Alexandria governorate were also determined. Three contact insecticides, namely malathion, pirimiphos-methyl and cypermethrin, were tested. Tarsal contact bioassays on filter paper were carried out on adults following FAO methods and concentration-mortality lines were estimated to determine the resistance ratios for each insecticide and population. The data from the monitoring of insects revealed that T. castaneum and S. oryzae were the most common species infesting wheat in both Alexandria granaries and mills. Populations of S. oryzae were generally more resistant to malathion than the populations of T. castaneum . However, T. castaneum populations were more resistant to pirimiphos-methyl than the S. oryzae populations. Both populations of T. castaneum and S. oryzae were susceptible to cypermethrin. The detected levels of insecticide resistance indicate that this phenomenon takes place and should be a concern in Egyptian populations of T. castaneum and S. oryzae requiring monitoring and design of resistance management practices. Highlights: Stored-product insects were surveyed in wheat storage facilities in Alexandria, Egypt. The most common species infesting wheat storage facilities were S. oryzae and T. castaneum . Levels of insecticide resistance were determined in Tribolium castaneum and Sitophilus oryzae. Sitophilus oryzae was more resistant to malathion and T. castaneum was more resistant to pirimiphos-methyl. Both T. castaneum and S. oryzae were susceptible to cypermethrin.